Promoting a development culture in your organization : using career development as a change agent - Simonsen, Peggy (Davies-Black Pub. Palo AltoUS, 1997)
Defines organizational culture and describes factors which are making changes in the culture necessary. Presents organizational career development as the change agent needed to create a development culture in today's workplace. Examines roles and respponsibilities in a development culture and presents the steps needed to implement the career development system that will build the development culture.